Occurrence, structure and bioactivity of 1,7-diarylheptanoids - Claeson Per (2018)
The 1,7-diarylheptanoids are a class of secondary plant metabolites characterised by the structural motif aryl-C7-aryl. Based on their chemical structures, the diarylheptanoids have been divided into five different groups: non-phenolic linear diarylheptanoids (Type I), phenolic linear diarylheptanoids (Type II), macrocyclic biarylheptanoids (Type III), macrocyclic diaryl ether heptanoids (Type IV) and diarylheptanoids with cyclised C7-chain (Type V). The literature up to October 1993 has previously been covered (Claeson et al. J. Indian Chem. Soc. 1994, 77, 509-521), and presently the literature of October 1993 - September 1999 has been reviewed. During the period of review, reports on a total of 114 diarylheptanoid structures (including 75 new natural products) have been retrieved from the literature. These structures, together with pertinent information on plant sources, biological activities and references, have been compiled. © 2002 Elsevier B.V. All rights reserved.